Natural History, Multimodal Management, and Quality of Life Outcomes of Trigeminal Schwannomas - Makarenko, Serge; Ye, Vincent; Akagami, Ryojo (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background Trigeminal schwannomas are the second most common among intracranial schwannomas. These can arise from anywhere between the root and the distal extracranial branches of the trigeminal nerve. Clinical presentation depends on location and size, including but not limited to facial hypesthesia or pain, headaches, dizziness, ataxia, and diplopia. Literature is strikingly scant discussing the natural history of these lesions, while the treatment goals are heavily dependent on tumor presentation. Management decisions must be individualized to each tumor and each patient, while attempting to maximize the quality of life. We present the natural history of these lesions as well as their management by surgical resection or radiation therapy, and report long-term quality of life outcomes.Methods Between 2001 and 2015, 24 patients (66.7% female) with trigeminal schwannomas were diagnosed and managed at Vancouver General Hospital. We analyzed the clinical presentation, surgical results, resection rates, patient quality of life, and complications. To complete the evaluation, we prospectively collected 36-Item Short Form Health Survey (SF-36) quality of life assessments for comparison.Results We identified 12 patients treated with a craniotomy and surgical resection, 4 were treated with radiation therapy, while 8 patients were followed by observation. Mean age of study cohort was 49.2 years (range, 23–79 years), and most patients presented with facial hypesthesia (54.2%) and headaches (37.5%), while 37.5% were incidental findings. There were no major differences in patient demographics between the three groups. Patients offered surgery had larger lesions (mean diameter, 3.4 ± 1.1 cm) when compared with those that were irradiated or observed, and were more likely to have extracranial extension. Overall patient quality of life improved following treatment (ΔSF-36 + 12.9) at 3.9 years.Conclusions The treatment goals of trigeminal schwannomas focus on improvement in neurologic symptoms, relief of mass effect, and preservation of cranial nerve function. We demonstrate that smaller lesions found incidentally with minimal symptoms can be followed safely with serial imaging, with 1 of 9 (11.1%) progressing to require treatment over the course of 7.1 years. Management of trigeminal schwannomas should be individualized with an involvement of a multidisciplinary skull base team.
Keywords: trigeminal; schwannoma; quality of life; radiation; surgery; observation